2017
DOI: 10.1063/1.4973085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth temperature on structural and electronic properties of ZnO thin films

Abstract: Abstract.The electronic and structural properties for RF magnetron sputtering deposited ZnO thin films grown on Si substrate was obtained by using X-ray diffraction (XRD) and reflection electron energy loss spectroscopy (REELS). XRD spectra show the intensity of the diffraction peak increases with increasing the growth temperature with (002) is strongest diffraction peak. The particle sizes for (002) are increase from 10.2 nm to 60.2 nm with increasing growth temperature from room temperature to 500 o C, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 13 publications
(19 reference statements)
2
2
0
1
Order By: Relevance
“…Regarding the inorganic thin film, although, in the powder form, ZnO shows a high crystallinity degree ( Figure 1A), as a MAPLE-deposited thin layer, ZnO exhibits an amorphous nature, most probably its thickness (70 nm) being responsible for this behavior. A similar result was obtained when this metal oxide was deposited as a thin film at room temperature, without annealing treatments [31].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Regarding the inorganic thin film, although, in the powder form, ZnO shows a high crystallinity degree ( Figure 1A), as a MAPLE-deposited thin layer, ZnO exhibits an amorphous nature, most probably its thickness (70 nm) being responsible for this behavior. A similar result was obtained when this metal oxide was deposited as a thin film at room temperature, without annealing treatments [31].…”
Section: Resultssupporting
confidence: 80%
“…nature, most probably its thickness (70 nm) being responsible for this behavior. A similar result was obtained when this metal oxide was deposited as a thin film at room temperature, without annealing treatments [31]. MAPLE-deposited layers were investigated from morphological point of view, their FESEM images at two magnifications (Figures 4 and 5) and AFM images ( Figure 6) evidencing the globular morphology specific to films obtained by MAPLE process [19,20].…”
Section: Resultssupporting
confidence: 74%
“…Tanecik boyutunun artması dolayısıyla dislokasyon yoğunluğunun azalmasıyla beraber, yarıiletken filmin kristal kalitesi artacaktır [29][30][31]. Buna göre, ZEu-02 filminin, diğer filmlere göre daha iyi kristallenen film olduğu söylenebilir (Tablo 1).…”
Section: Bulgular Ve Tartışmaunclassified
“…As per the calculation, it was found that the grain size of the samples increased with the pyrolysis temperature. Tahir et al [46] observed high-intensity peaks of XRD with the increase in growth temperature. They found the polycrystalline nature of ZnO with their preferred orientation of (002) plane with the highest peak for the films deposited at 500 °C.…”
Section: Structural Analysismentioning
confidence: 99%